Calculus

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: x ∂y ∂ 2z ∂ ∂z = = f12 (x, y ) = fxy (x, y ). ∂y∂x ∂y ∂x ÀÐÙØ ÐÐ ×Ø ÙÖÒ Ö ÐÒ f11 (x, y ) Ó f22 (x, y ) Ö ÐÙØ ÙÖº Ä ØÙÑ ÐÐ ×Ø Ö ÒÖ ÐÙØ ÙÖ Ó f12 (x, y ) Ó f21 (x, y ) ÙÖ º Ë ØÒ Ò º ÔÙÒ Ø f (x, y ) ÖÙÑ Ö Ò Ö ÚÖ ÝÖ Ö ÐÐ × Ñ ÐÙØ Ó Ö× Ö× Ù ÐÖ ÙÖÒ ÐÐ P = (a, b) º f21 (x, y ) × Ù ÐÐ Ö × ÐÖ D D ÙØ Ò ÙÑ Ö f1 (x, y )¸ f2 (x, y )¸ f12 (x, y ) Ó Ö × Ñ ÐÐ Ö Dº ÐÖ ÒØ ÓÔ ÒÒ × f12 (a, b) = f21 (a, b). º ÀÙ ÑÝÒ ØÐ ÙÐ × ×Ø ÐÖ Ò Ú ÖÒ Ñ × Ð Ö Ò Ò Ùº ¾º ×Ø × × ÐÙØ ÐÖ Ò ÐÙØ Ë ÐÖ ÐÐ ÙÖ ÒÒ Ù Ö ÖÖ º ×Ø Ñ Ò ØÚ ÙÑ ØÚ ÑÙÖ Ò ¾¸ Ø Ð ÙÐ Ö ÝØÙѺ ×Ò ÒÒ ØØ Ö ÙÖ ÝÖ Ö Ñ× w= f (x, y, z ) ∂ 3w ∂x∂y 2 Ó ´ Ð ÝÖ×Ø ØÚ ×Ú Ö ÑºØºØº y¸ ×ÚÓ ÒÙ × ÒÒ ÑºØºØº xµ ∂ 3w ∂y∂z∂y ´ Ð ÝÖ×Ø ÑºØºØº y¸ ×ÚÓ ÑºØºØº z Ó ÐÓ ÙÑ ÑºØºØº y µ. Ö ÙÑ Ö ÐÐ ÐÐ Ó Ö Ö º Ë ØÒ Ò º ×Ñ ÐÙØ Ö× ÐÖ ÙÖ ´ ÒØ ÐÑ ÒÒ ÓÔ ÒÒ ÔÙÒ ØÙÑ Ø Ë ØÒ Ò Ù Ö×Ñ Ö ÝØ ×Ø ÙÖ Ð ÖÙÑ Ö Ö Ö Ð Öº ×Ø º µ Ä ØÙÑ Ñ ÖÙ × ÒÖ ÐÙ ÙØ Ò ÙÑ ÔÙÒ Ø fÚÖ ÐÐ n P = (x1 , x2 , . . . , xn )º Ø ÐÐ Ø Ø Ð × ÑÙ ×× Ö ÐÙØ Ò Ö Ê ÙÖ ÐÖ Ö ÝØ ×Ø Ö ÝØ ×Ø Ë Ó ÙÑ ØÚ Ö f P Ó P ÒÓØÑ ÔÙÒ Ø ÒÙÑ Ø ÐÐ Ø Ø Ð ÐÐ Ö ÐÙØ Ú ÖÖ Ö ÐÙØ ÖÙ × Ñ Ó ×Ñ D D ½º Ò ÖÙ ÙÖÒ Ö × Ñ Ú ×Ó Pº ÒÚ Ð ÙÖ º Å ÐÐ Ö Ö ¾¼¼ ËØ Ö Ö º¼ Ë ØÒ Ò º Ð Ö ÐÐ ÒÐ ´Ã ÙÖ ÐÒ ÒÒ Ø ÔÙÒ Ø ÒÙÑ u = g (x) (f ◦ g )(x) = f (g (x)) Ð ºÃ ÙÖ Ö ÝØ ×Ø ÐÐ Ø Ö Ò Ò ÁÁ Ð Òº Ö ºµ ÖÙÑ Ö × Ð ÒÐ ÝÖ Ö Ø ÔÙÒ Ó ÒÐ g (x) Ó f (u) Ø ÒÙÑ xº ÐÐ × x (f ◦ g )′ (x) = f ′ (g (x))g ′ (x). º½ Ã Ö ÝØÙ ÝÖ×Ø ÐÐ Ò ×Ø ÙÖ Ð Áº t¸ × Ó ÐÙØ Ä ØÙÑ ÙÖ f (x, y ) ÐÖ Ð Ò ÒÐ ÚÖ ÖÓ ÐÐ ×Ñ Ö×Ñ ÐÐ Öº x = x(t) ÖÙÑ Ö ÖÙÑ Ö ÝÖ Ö ÓÔ ÒÒ × Ù ÙÑ ÔÙÒ Ø ÒÙÑ y = y (t) ÖÙ (x(t), y (t)) × Ù Ó ÝÖ Ö ÐÐ Ö f × ÒÒ Ö ÑÙÖ Ö ÐÐ x(t) y (t) ×Ù ÔÙÒ Ø ÒÙÑ tº g (t) = f (x(t), y (t)) Ð ÒÐ Ø t Ó g ′ (t) = f1 (x(t), y (t))x′ (t) + f2 (x(t), y (t))y ′ (t). º¾ à tº Ö ÙÖ Ð ÁÁº Ê ØÙÑ z = f (x, y) Ö× Ñ x = x(t) Ó y = y (t) ÖÙ ÐÐ Ö ÝØÙ dz ∂z dx ∂z dy = + . dt ∂x dt ∂y dt º¿ à ÐÐ ÙÖ Ð ÁÁÁº Ä Ö ÝØÙÑ ØÙÑ Ö f (x, y ) × ÚÖ ÐÐ Ö ÝØ ×Ø Ó Ö ÙÑ x Ó y ×Ñ ØÙÖ ÖÙ s Ó t¸ x = x(s, t) y = y (s, t)º Ê ØÙÑ ×ÚÓ g (s, t) = f (x(s, t), y (s, t)). Ð Ö´ ÒÙÑ × Ñ ÖÐ ÙÑ × ÐÝÖ ÙÑ Ó º½µ g1 (s, t) = f1 (x(s, t), y (s, t))x1 (s, t) + f2 (x(s, t), y (s, t))y1 (s, t), Ó g2 (s, t) = f1 (x(s, t), y (s, t))x2 (s, t) + f2 (x(s, t), y (s, t))y2 (s, t). ºÃ Ö ÝØÙÑ ÙÖ Ð Áκ Ê ØÙÑ z = f (x, y) s Ó Ö× Ñ x = x(s, t) Ó y = y (s, t) ÖÙ ÐÐ tº Ö ∂z ∂x ∂z ∂y ∂z = + ∂s ∂x ∂s ∂y ∂s ∂z ∂z ∂x ∂z ∂y = + . ∂t ∂x ∂t ∂y ∂t Ó ºÃ Ö ÝØÙÑ ÙÖ Ð Îº Ê ØÙÑ z = f (x, y) s Ó Ö×Ñ x = x(s, t) ∂x ∂s ∂y ∂s ∂x ∂t ∂y ∂t Ó y = y (s, t) ÖÙ ÐÐ tº Ö ∂z ∂s ∂z ∂t = ∂z ∂x ∂z ∂y ½¼ ºÃ ÙÖ Ð ÎÁº Ä m Ö ×Ñ ØÙÑ Ñ ÖØ × Ñ ÐÐ ∂xi ∂u Ó × ÙØÐÓ ∂xi ∂tj ×Ø uÚ Ö ÐÐ n ÝØÙÑ t1 , t2 , . . . , tm º ÐÐ ...
View Full Document

This note was uploaded on 01/31/2011 for the course MATH 203 taught by Professor Röggi during the Spring '10 term at Uni. Iceland.

Ask a homework question - tutors are online